PERANAN METODE DISKUSI DALAM PEMBENTUKAN KARAKTER MAHASISWA MELALUI MATA KULIAH PENDIDIKAN KEWARGANEGARAAN (PKn) - Saputra, Edi (TINGKAP, 2015)
In the current civics lesson, students often experience boredom and tends to just lecture to simply look for value alone. This is due to the material being taught monotonous, theoretical, cognitive nature, even verbalistic. In the course it appears that the students just come, sit down, shut up and go home and some have fallen asleep. Although the discussion of the methods applied in lectures, but students and lecturers are more likely to lead to the questioning, rarely exchanging information, let alone understanding, not able to analyze and comment on the information that is different, and not many are active but more so the audience, so the ability critical thinking and interpersonal skills difficult to achieve. This resulted in "disruption" process of character formation of students as embodied the vision, mission, and goals of the Civic Education. For that one of the efforts is to develop a simple method and a simple discussion, starting from the preparation phase, the implementation phase and the closing phase. Keywords:Â  Development, Discussion Method, Citizenship Education, Student Character